“There Are Not Enough Lawyers, and There Are Not Enough Financial Resources”: Canadian and American Intimate Partner Violence Service Providers’ Perspectives for Better Supporting Immigrant Women Survivors - Slakoff, Danielle C. (Crime & delinquency, 2024)
Immigrant women are at a high risk of intimate partner violence (IPV) and experience many challenges to help-seeking. Currently, little is known about IPV service providers’ perspectives for better supporting immigrant women within their agencies. Drawing on an intersectional framework, constructivist grounded theory (CGT) with a modified written vignette technique was employed. Online surveys were used to gather service providers’ perspectives on the vignette, which described an immigrant woman experiencing IPV. Responses from over 50 IPV service providers in the U.S. and Canada indicated the need for enhanced training to aid immigrant survivors. Further, several respondents recommended changes to the immigration/legal systems, as well as more resources for community outreach and language, legal, and housing support.